Strategi Komunikasi Coffee 89 Dalam Membangun Citra Positif di Masyarakat - Nuril Anwar Sutisna; M.Mujahidin; Rizky Esa; Tb.Ade Rachmat; Agus Facturohman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The growth of the coffee shop business in Indonesia has increased very rapidly. The growth of the coffee shop business does not only occur in big cities, but has also penetrated into small cities, one of which is Serang City. The proliferation of coffee shops in Serang City requires business people to implement effective marketing communications to achieve business goals. This research analyzes the marketing communication strategies implemented by three coffee shops in Serang City, namely Kalanoia Coffee, Aish Coffee Serang City, in attracting consumer buying interest. Using a qualitative approach and descriptive method, data was collected through interviews, observation, and documentation, then analyzed with the 7P Marketing Mix concept (Product, Price, Place, Promotion, People, Process, Physical Evidence). The results showed that the three coffee shops carried out marketing communication strategies in attracting consumer buying interest. The strategy is carried out through social media as a promotional medium, providing various promo programs to attract buying interest, and collaboration with influencers to expand market reach. Although each applies a different approach according to their characteristics and target market. All three have their own uniqueness that can differentiate them from competitors.